The double-height duplex The influence of Le Corbusier in Lima, Peru - Krateil Fuentes, Alejandro (2025)
The duplex with double height is an intriguing and underutilized housing typology that stands out by doubling the internal height of the apartment, facilitating the spatial connection between environments on different levels. Unlike the flat typology, characterized by a single horizontal space, the duplex with double height offers a distinctive spatial alternative. This research focuses on uncovering the history and characteristics of the duplex with double height as an option to improve spatial quality. In Lima, the influence of Le Corbusier is reflected in forty buildings that adopt this typology, combining classical and contemporary architectural solutions. The methodology used included searching for projects in Lima with this characteristic and conducting interviews with architects and users. The opinions were analyzed using the ATLAS.ti software, and the conclusions reflect the motivations for adopting this typology as part of Lima’s modern built heritage.